2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594184
|View full text |Cite
|
Sign up to set email alerts
|

I Can See Your Aim: Estimating User Attention from Gaze for Handheld Robot Collaboration

Abstract: This paper explores the estimation of user attention in the setting of a cooperative handheld robot -a robot designed to behave as a handheld tool but that has levels of task knowledge. We use a tool-mounted gaze tracking system, which after modelling via a pilot study, we use as a proxy for estimating the attention of the user. This information is then used for cooperation with users in a task of selecting and engaging with objects on a dynamic screen. Via a video game setup, we test various degrees of robot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Efforts towards involving user perception in the robot's task planning were made in our recent work on estimating user attention [3]. The method was inspired by work from Land et al who found that human's eye gaze is closely related to their manual actions [8].…”
Section: A Handheld Robotsmentioning
confidence: 99%
See 3 more Smart Citations
“…Efforts towards involving user perception in the robot's task planning were made in our recent work on estimating user attention [3]. The method was inspired by work from Land et al who found that human's eye gaze is closely related to their manual actions [8].…”
Section: A Handheld Robotsmentioning
confidence: 99%
“…2: The Handheld robot used for our study. It features a set of input buttons and a trigger at the handle, a 6-DoF tip and user perception through gaze tracking as reported in [3].…”
Section: Human Gazing Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…As a starting point of addressing this problem, extended user perception can be introduced to allow the robot to estimate the user's point of attention via eye gaze in 3D space during task execution [3]. An estimate of users' visual attention informs the robot about areas of users' interest.…”
Section: Introductionmentioning
confidence: 99%